EFEKTIVITAS PENERAPAN PENDEKATAN DEEP LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS V SD NEGERI 2 AMBON - Rahaningmas, Rofika Azzahra; Ode Abdurrachman; Leonid Ritiauw (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the application of the Deep Learning approach in improving student learning outcomes in the subject of Natural and Social Sciences (IPAS) for grade V at SD Negeri 2 Ambon. In this study, there was a low learning outcome of students in IPAS due to the approach used in learning, namely the traditional teaching approach that did not actively involve students. The Deep Learning approach was applied as a solution, by emphasizing meaningful learning, mindful learning, and joyful learning. The method used was quantitative with a one-group pretest-posttest design. The research sample was 20 students in class VA. Data collection techniques included observation, questionnaires, tests (pretest and posttest), and documentation. The instruments were tested for validity and reliability before being used. The results of the questionnaire data analysis with the N-Gain test showed that the g value was 0.79. The value of 0.79 is in the range of 0.70 ≤ g ≤ 100. The value of 0.079 is in the